DRIED FISH CAKES WITH IMPROVED TEXTURE - BASU, SUBRATA; GUPTA, S. S.; RAO, C.C. PANDURANGA (Journal of Indian Fisheries Association, 2015)
To overcome the problem of underutilization of marine by-catches,Basu et al. (1985) developed fish cube from minced fish meat. Althoughthe product was acceptable, it had little rubbery texture. An attempt wasmade to improve the texture of the cake by several methods. It was foundthat 5% tapioca starch along with 3% texturised soyabean proteinimproved the texture and juiciness of the rehydrated product. Preheatingof the minced meat at 70Â°C for 30 minutes also improved the textureappreciably. It was also found that mixing of the ingredients at low speed(less than 100 rpm) in a dough mixer gave the best texture, higher speedand sharp blades leading to rubbery texture. The dehydrated product(moisture 19-20%) thus prepared had a shelf life of six months at ambienttemperature.